قواعد في اللغة الأكادية - شحود أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
عُرفت اللغة الأكادية في منطقة بلاد ما بين النهرين في نهاية الألف الثالث وبداية الألف الثاني قبل الميلاد, وهي إحدى لغات الأسرة السامية وبرزت بوصفها عاملاً مهماً في المنطقة. وقد انطوت هذه اللغة تحت لهجاتٍ عدة هي: البابلية القديمة والبابلية الوسيطة والبابلية الحديثة والبابلية المتأخرة والبابلية النموذجية والآشورية القديمة والآشورية الوسيطة والآشورية الحديثة. وكُتبت معظم نصوص هذه اللغة بمِرْقَم قصبي على ألواحٍ طينيةٍ, ونظامها الإشاراتي كان إرثاً سومرياً. واعتمدت قواعد لغويةً مشابهةً للغة العربية من حيث استخدامها للأسماء والأفعال والضمائر والأوزان. كما تخصصت اللغة الأكادية في تحديد الجنس لغوياً مذكراً ومؤنثاً وفي تحديد حالات الرفع والنصب والجر والمفرد والتثنية والجمع. The Akkadian Langauge had flourished in Mesopotamia at the end of the third millennium and beginning of the second millennium BC. It is needless to say that it belongs to the Semitic Family, and had appeared as a remarkable factor in the area. It consisted of many dialects such as: the ancient Babylonian, the Mid-Babylonian, the Modern Babylonian, the Late Babylonian, the Typical Babylonian, the Ancient Assyrian, the Mid-Assyrian and the Modern Assyrian. It had been inscribed by a wooden tool on clay tablets, and its sign system had been a Sumerian Heritage. It had adopted linguistic rules very similar to those of the Arabic Language, regarding the use of nouns, verbs, pronouns, and meters. However, the Akkadian had specialized in identifying the gender, linguistically speaking, masculine or feminine, and in identifying the case of verbal, nominal, genitive, dual and the plural.